(untitled) (Indian Journal of Nematology, 2024)
Distolabrellus vulvatus sp. n. was collected from decaying leaves in a ditch at faculty of agriculture, Aligarh Muslim University. The new species is characterized by a medium size and slender female body with L = 746-1326 μm; a = 15.8-23.2; b= 5.0- 7.2; c = 11.0-18.4. Lips dimorphic, prominent, transverse and fine longitudinal body striations, prominently swollen metastegostom bearing three, simple, setose denticles. Vulva far posterior with surrounding cuticular flap. Spicules straight, fused distally and gubernaculum almost straight, tapering towards proximal end, distal end broad, notched.